2004
DOI: 10.1080/02571862.2004.10635067
|View full text |Cite
|
Sign up to set email alerts
|

Soil mineralogy research in South Africa, 1978 to 2002 - a review

Abstract: Over 160 publications that contain mineralogical information were produced in the last 25 years of which about half were published in national and international journals. In many articles mineralogical data were presented but not discussed. Most studies were concerned with the clay fraction and X-ray diffraction was the dominant technique used for mineral identification. The investigations covered a very wide range of topics such as inheritance of clays from parent materials, and broad regional studies at Lusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Unfortunately, many soil fertility studies have hardly considered the role of soil mineralogy in understanding soil fertility and nutrient dynamics in agro ecosystems [21]. The lack of integrated soil mineralogy-soil fertility studies is indicated by the lack of interest by soil fertility researchers in carrying out detailed soil mineralogical studies [22] and also the tedious processes involved in characterization, identification and quantification of clay minerals. Another reason is the lack of inexpensive and rapid spectroscopic techniques for soil characterization, especially in developing countries [23].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many soil fertility studies have hardly considered the role of soil mineralogy in understanding soil fertility and nutrient dynamics in agro ecosystems [21]. The lack of integrated soil mineralogy-soil fertility studies is indicated by the lack of interest by soil fertility researchers in carrying out detailed soil mineralogical studies [22] and also the tedious processes involved in characterization, identification and quantification of clay minerals. Another reason is the lack of inexpensive and rapid spectroscopic techniques for soil characterization, especially in developing countries [23].…”
Section: Introductionmentioning
confidence: 99%
“…Feldspar is broken down by carbonic acid from rain, releasing K. Under severe weathering conditions, kaolinite, a near chemically-inert clay mineral, may form from weathering products (Wilson, 1999). Micas (sheet silicates) also occur in metamorphic rocks, such as shale (Bühmann et al, 2004a(Bühmann et al, , 2004b. On weathering, mica degrades into interstratified forms such as chlorite and vermiculite, releasing K in the process (Wilson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The similarity between the cohesion and the plasticity of the soil could be attributed to the mineralogical make up of the soil. Noting that clay minerals are common with soils derived from argillaceous materials and such soils are associated with high plasticity and high cohesion (Bühmann et al, 2004; Emeh and Igwe, 2018).…”
Section: Geotechnical Propertiesmentioning
confidence: 99%